Discrete event simulation for the purpose of real-time performance evaluation of distributed hardware-in-the-loop simulators for autonomous driving vehicle validation - Funda, Christoph; Hielscher, Kai-Steffen; German, Reinhard (Electronic Communications of the EASST, 2021)
Hardware-in-the-loop test benches are distributed computer systems including software, hardware and networking devices, which require strict real-time guarantees. To guarantee strict real-time of the simulator the performance needs to be evaluated. To evaluate the timing performance a discrete event simulation model is built up. The input modeling is based on measurements from the real system in a prototype phase. The results of the simulation model are validated with measurements from a prototype of the real system. The workload is increased until the streaming source becomes unstable, by either exceeding a certain limit of bytes or exceeding the number of parallel software processes running on the cores of the central processing unit. To evaluate the performance beyond these limits, the discrete event simulation model needs to be enriched by a scheduler and a hardware model. To provide real-time guarantees an analytical model needs to be built up.